Penguatan Budaya Kerja Menuju Sekolah Efektif Di Smp Negeri 4 Klaten - Sukma Handayani, Udi; , Prof.Dr. Bambang Sumardjoko,M.Pd; , Dr. Sabar Narimo, M.M., M.Pd (2016)
This study aims to: (1) Describe the work culture which takes place in SMP Negeri 4 Klaten in towards effective schools. (2) Describe the efforts of the school in maintaining a work culture in SMP Negeri 4 Klaten in towards effective schools. (3) Describe the constraints identified to maintain the culture of work in SMP Negeri 4 Klaten in towards effective schools. This type of research is qualitative research design using an ethnographic approach. The results of the study, (1) Strengthening the work culture which takes place in SMP N 4 Klaten in towards effective school looks already organized and orderly. Penerpan or execution of the work culture even been scheduled, with one culture to be characteristics or junior high school kharateristik N 4 is cultural klaten 3 S (Smiles Salam Sapa). (2) Characteristics of vigorous foundations on strengthening the work culture in SMPN 4 Klaten, in order to maintain work culture towards effective schools, this is indicated by the morale of teachers is very good it can certainly support the implementation of learning activities, teachers and employees apply culture of discipline to keep it together through a lot of ways of mounting board pamphlet written schedule announcements strict sanctions even though still mengedepakan cultural kinship. (3) Barriers are found such as, infrastructure srana factors, the character of citizens of different schools, limited mastery of technological advances and many other obstacle.